Connectivity in the Criminal Justice System: Jurisdictional Issues Between Civilian and Military Courts - Arter Lukas Tulia (CV. Era Digital Nusantara, 2026)
This study critically examines the adjudicative competence over connectivity offenses involving both civilian and military actors. The persistent jurisdictional ambiguity frequently causes significant legal uncertainty within the criminal justice system. Normatively, jurisdiction is determined by assessing the predominant loss, whether it impacts public or military interests. Although the Indonesian National Armed Forces Law mandates jurisdictional separation, its practical implementation remains heavily constrained by the ongoing stagnation of military court reform. Employing a normative juridical method with statutory, conceptual, and case approaches, this research analyzes the recent acid attack against the activist Andrie Yunus . The findings reveal that determining adjudicative authority strictly requires comprehensive joint investigations by civilian and military prosecutors. Furthermore, because this specific case fundamentally harmed public interests, transparency dictates that it must be adjudicated directly within the national civilian justice system. Resolving this institutional conflict demands immediate legislative harmonization to ensure absolute legal accountability and public institutional trust.